The Influence Of Business Ethics, Code Of Conduct, Shareholders And Good Corporate Governance (GCG) Policy On The Implementation OF GCG In Bank Sumut - Karina Sari (International Journal of Applied Finance and Business Studies, 2021)
This research goal is to analyze the influence of business ethics, code of conduct, shareholder and Good Corporate Governance (GCG) policy toward the implementation of GCG at Bank of North Sumatra.The type of research used is the study of causal associative, with a sample of 50 respondents from the employees of Bank of Sumut. The type of data is primary, directly obtained from questionnaires that are sent to respondents. The analysis method that is used in this research is multiple regression analysis. Data quality was authentically tested by validity and reliability test data. Classical assumption tests that are used are normality and heteroscedasticity tests. Furthermore, the significance partial test (t-test) and coefficient of determination test (R2) are used for the hypothesis test. The results of this research shows that business ethics, code of conduct and GCG policy were partially and positively affect the implementation of GCG at Bank of North Sumatra; however, shareholders have no significant impact on the implementation of GCG at the Bank of North Sumatra.